Cultural adaptation and reliability of “bullying in nursing education questionnaire” in nursing university students - Kalafati, Maria; Nieri, Alexandra Stauvroula; Dede, Maria Niki; Tziaferi, Styliani; Karanikola, Maria; Mpouzika, Meropi; Lemonidou, Chryssoula (My University, 2019)
Introduction: Bullying is a phenomenon observed in nursing students and it seems to have negative effects on physical and mental health. Aim: Cultural adaptation in Greek language and reliability of the questionnaire "Bullying in Nursing Education Questionnaire (BNEQ)" in Greek Students of Nursing. Material and Method: A methodological, prospective, quantitative and correlational study was conducted in a convenient sample of 25 nursing university students. The BNEQ was translated from English into Greek, and backward, and its cultural adaptation took place. Cronbach's α and test-retest reliability (Wilcoxon, Spearman) were applied at statistical significance α=0.05 (SPSS-ver24.0). Results: The Cronbach alpha coefficient was equal to 0.96. All questions were significantly correlated (p [removed] 0.05) between the first and second phase, with the exception of the questions "Yelling or shouting in rage to you from…", "Inappropriate, nasty, rude or hostile behavior to you from…", and "Negative or disparaging remarks about becoming a nurse…". Conclusions: The pilot data support the reliability of the BNEQ scale in Greek language. However, they should be confirmed in a larger sample. © 2019, Hellenic Nurses Association. All rights reserved.
Keywords: BNEQ; Bullying; Nursing school; Reliability; Students; Validation